Methodology enhancement for determining parameters of room systems when mining uranium ore in the SE “SkhidGZK” underground mines, Ukraine - Stupnik, Mykola; Kalinichenko, Vsevolod; Fedko, Mykhaylo; Pysmennyi, Serhii; Kalinichenko, Olena; Pochtarev, Alexey (Mining of Mineral Deposits, 2022)
Purpose. The present paper aims to enhance methodology for determining the safety and stability parameters of room mining systems with backfilling of the mined-out area when mining uranium ores in underground mines of the State Enterprise “Skhidnyi Mining and Beneficiation Plant” (SE “SkhidGZK”). Methods. The analytical research method used in the presented paper includes the analysis of previous relevant instructions and reports on the research performed at the SE “SkhidGZK”, as well as publications on the subject, operational geological survey documentation containing monitoring data on the stress-strain state of the rock mass surrounding the formed cavities and the actual state of the mined-out blocks in all underground mines of SE “SkhidGZK”. Findings. The research performed enables development of a new instruction for determining the safety and stability parameters of the room systems with backfilling when mining uranium ores in the SE “SkhidGZK” underground mines. Based on the developed new instruction, the stability of outcrops in mined-out rooms has been calculated, considering the actual time of their life. The obtained parameters fully correspond to actual stability of rooms in blocks of all underground mines. This indicates that the new instruction is more advanced as compared to the current Instruction and its implementation will contribute to mine safety enhancement. Originality. The increased depth of mining uranium ore in the SE “SkhidGZK” underground mines and the increase in lifetime of mined-out rooms require regular adjustment of the methodology for determining their safety and stability parameters. Based on the accumulated production experience, the observations conducted and a thorough analysis of the actual state of cavities, new and adjusted current dependences have been obtained that more accurately consider the impact of both determined factors and those unprovisioned in the current Instruction for determining the safety and stability parameters of rooms. Practical implications. The advanced methodology for determining the safety and stability parameters of room systems in comparison with the methodology described in the current Instruction at the “SkhidGZK” underground mines provides higher accuracy when determining the design parameters of rooms in the stoping blocks and greater reliability of predictive stability of both individual outcrops and rooms in general.